2006
DOI: 10.1016/j.neuroscience.2005.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the rat brain during sleep deprivation and recovery sleep: an Affymetrix GeneChip® study

Abstract: Previous studies have demonstrated that macromolecular synthesis in the brain is modulated in association with the occurrence of sleep and wakefulness. Similarly, the spectral composition of electroencephalographic activity that occurs during sleep is dependent on the duration of prior wakefulness. Since this homeostatic relationship between wake and sleep is highly conserved across mammalian species, genes that are truly involved in the electroencephalographic response to sleep deprivation (SD) might be expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
128
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 35 publications
(58 reference statements)
12
128
2
5
Order By: Relevance
“…Spontaneous sleep-wakefulness or natural sleep is less well studied, based on the short, rapid cycling of sleep-wake bouts in rodents, the requirement to dissociate circadian and homeostatic influences, and the possible effects on cellular activities resulting from the practical difficulty of sacrificing a sleeping animal without first waking him up. Such technical considerations further elaborate the complexities involved in studies designed to understand the intracellular response to sleep.More recent microarray analyses showed that a small percentage of genes (i.e., 1-5%) were differentially expressed across sleep and waking states, independent of the time of day (TOD) or the brain region studied [Cirelli et al, 2004;Terao et al, 2006]. These patterns were conserved across rodent species [Terao et al, 2006] and encoded proteins associated with a variety of housekeeping functions, including energy metabolism, synaptic plasticity, membrane trafficking and maintenance, and cholesterol biosynthesis [Cirelli et al, 2004;Terao et al, 2006].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Spontaneous sleep-wakefulness or natural sleep is less well studied, based on the short, rapid cycling of sleep-wake bouts in rodents, the requirement to dissociate circadian and homeostatic influences, and the possible effects on cellular activities resulting from the practical difficulty of sacrificing a sleeping animal without first waking him up. Such technical considerations further elaborate the complexities involved in studies designed to understand the intracellular response to sleep.More recent microarray analyses showed that a small percentage of genes (i.e., 1-5%) were differentially expressed across sleep and waking states, independent of the time of day (TOD) or the brain region studied [Cirelli et al, 2004;Terao et al, 2006]. These patterns were conserved across rodent species [Terao et al, 2006] and encoded proteins associated with a variety of housekeeping functions, including energy metabolism, synaptic plasticity, membrane trafficking and maintenance, and cholesterol biosynthesis [Cirelli et al, 2004;Terao et al, 2006].…”
mentioning
confidence: 99%
“…These patterns were conserved across rodent species [Terao et al, 2006] and encoded proteins associated with a variety of housekeeping functions, including energy metabolism, synaptic plasticity, membrane trafficking and maintenance, and cholesterol biosynthesis [Cirelli et al, 2004;Terao et al, 2006]. In addition, a subset of state-dependent mRNAs was common to two or more brain regions [Cirelli et al, 2004;Terao et al, 2006], suggesting that sleep influences global as well as regional brain function(s). While these studies provided valuable insights regarding the intracellular impact of sleep at the nucleic acid level, alterations in mRNA levels often do not reflect corresponding protein expression [Anderson and Seilhamer, 1997;Abbott et al, 1999;Gygi et al, 1999;Ideker et al, 2001;Takahashi, 2004], a more direct functional indicator of the cellular response to sleep.…”
mentioning
confidence: 99%
See 3 more Smart Citations